2020
DOI: 10.1155/2020/4582459
|View full text |Cite
|
Sign up to set email alerts
|

Circulating CD14+HLA‐DR−/low Myeloid‐Derived Suppressor Cells as Potential Biomarkers for the Identification of Psoriasis TCM Blood‐Heat Syndrome and Blood‐Stasis Syndrome

Abstract: Psoriasis is a chronic autoimmune disease. Identification of the biomarkers responsible for Traditional Chinese Medicine (TCM) syndromes of psoriasis can help researchers recognize the different aspects of psoriasis and find novel therapeutic targets for the treatment of psoriasis. The current study investigated the levels of circulating Mo-MDSCs and Mo-MDSC-associated immune factors in the peripheral blood of psoriasis patients with different TCM syndromes. We found that the frequency of Mo-MDSCs (CD14+HLA-DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In recent years, CD14 + HLA-DR-/low M-MDSCs have been reported to suppress T-cell activation ( Lauret Marie Joseph et al, 2020 ). In psoriatic patient PBMC, M-MDSCs was increased, compared to the healthy control ( Soler et al, 2016 ; Sun et al, 2020 ). In vivo and in vitro assays demonstrated that Treg cells induced by M-MDSCs in the PBMC of a psoriasis patient presented suppressive functionality reduction.…”
Section: Discussionmentioning
confidence: 85%
“…In recent years, CD14 + HLA-DR-/low M-MDSCs have been reported to suppress T-cell activation ( Lauret Marie Joseph et al, 2020 ). In psoriatic patient PBMC, M-MDSCs was increased, compared to the healthy control ( Soler et al, 2016 ; Sun et al, 2020 ). In vivo and in vitro assays demonstrated that Treg cells induced by M-MDSCs in the PBMC of a psoriasis patient presented suppressive functionality reduction.…”
Section: Discussionmentioning
confidence: 85%
“…Icariin has a therapeutic effect on coronary heart disease, but its mechanism remains largely unclear. According to TCM principles, ventricular dysfunction and heart failure arise from Qi deficiency and blood stasis [ 36 , 37 ]. In this study, icariin therapy exhibited notable improvements in LVEF and FS while concurrently reducing LVEDD and LVESD compared to the MI group.…”
Section: Discussionmentioning
confidence: 99%
“…69,70 As advances are made in the understanding of mRNA regulation in psoriasis, opportunities will arise for more accurate monitoring and efficacious intervention. 69,71,72 Exclusive discussion of pharmacology creates an incomplete picture of the advances made in psoriasis management. Understanding and combating poor medication adherence is essential to improving clinical outcomes.…”
Section: Psoriasis Pharmacology In Broader Contextmentioning
confidence: 99%